2015
DOI: 10.1186/s40175-015-0033-7
|View full text |Cite
|
Sign up to set email alerts
|

Integrating mobile phone technologies into labor-market intermediation: a multi-treatment experimental design

Abstract: This study investigates the causal impacts of integrating mobile phone technologies into traditional public labor-market intermediation services on employment outcomes. By providing faster, cheaper and up-to-date information on job vacancies via SMS, mobile phone technologies might affect the rate at which offers arrive as well as the probability of receiving a job offer. We implement a social experiment with multiple treatments that allows us to investigate both the role of information channels (digital versu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 40 publications
(43 reference statements)
1
23
0
Order By: Relevance
“…Therefore, appropriate technologies that can intermediate between demand and supply of labour will have a significant impact on the overall economic participation of individuals. For instance, a study by Dammert et al, (2015) on mobile phone technology and labour market intermediation highlights that through faster, cheaper and up-to-date information on job vacancies via SMS and mobile technologies, individuals are able to effectively participate in the labour market. Greene and Mamic (2015) further highlight that there is a changing dynamic in the world of work, such that the proliferation of information through communication technology (like mobile technology) is playing a central role in boosting productive activities.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Therefore, appropriate technologies that can intermediate between demand and supply of labour will have a significant impact on the overall economic participation of individuals. For instance, a study by Dammert et al, (2015) on mobile phone technology and labour market intermediation highlights that through faster, cheaper and up-to-date information on job vacancies via SMS and mobile technologies, individuals are able to effectively participate in the labour market. Greene and Mamic (2015) further highlight that there is a changing dynamic in the world of work, such that the proliferation of information through communication technology (like mobile technology) is playing a central role in boosting productive activities.…”
Section: Review Of Literaturementioning
confidence: 99%
“…However, as seen in Table 9, out of the 10 different interventions, only one (Jensen, 2012) finds a significant impact on employment, increasing employment by 2.4 percentage points over 3 years. Dammert et al (2015) find their intermediation services tend to speed up the process of finding a job, with a significant employment impact after 1 month, but by 3 months the control group has caught up. Many of the other studies have small, but positive, point estimates, with an average impact across the studies of 2.7 percentage points.…”
Section: Search and Matching Assistancementioning
confidence: 98%
“…These incorporate several types of specific interventions. The work that tests public intermediation services most directly is Dammert et al (2015), who worked with the public service provider in Peru to test whether providing information about job vacancies to registered job seekers improves employment, and additionally whether sending these announcements by SMS message helps further. Another example of providing information about job opportunities and recruiting services is Jensen (2012), who connected rural villages in India to experienced recruiters at the start of the business process outsourcing boom in India, providing information about this new sector.…”
Section: Search and Matching Assistancementioning
confidence: 99%
“…Dammert et al (2014) suggested that there is a positive and significant short-term effect on employment for public labor market intermediation.…”
Section: Smartphone Technologymentioning
confidence: 99%
“…The unprecedented expansion of Information and Communication Technologies (ICT) in the last two decades however has enabled and shaped the existence of a new array of labor market intermediaries, such as online job boards, social media sites, and e-recruiting firms, which have invigorated research in this area (Dammert et al, 2014). The growth in Internet revolutionized the way people communicate with one another.…”
Section: Introductionmentioning
confidence: 99%